Frequency of intake and amount of fluoride in milk for remineralisation of artificial caries on enamel and dentine: Ex vivo/in situ study - Cassiano, Luiza; Pessan, Juliano [UNESP]; Comar, Livia; Levy, Flavia; Cardoso, Cristiane; Dionisio, Aline; Manarelli, Michele [UNESP]; Grizzo, Larissa; Magalhães, Ana Carolina; Buzalaf, Marília (Elsevier, 2017)
Objectives This study analysed the effect of frequency of intake and amount of fluoride in milk on the remineralisation of artificial enamel and dentine caries lesions ex vivo/in situ. Materials and methods Pre-demineralised bovine enamel and dentine slabs were randomly allocated into 5 groups and fixed in removable appliances used by subjects for 7 days in each phase. Each treatment comprised milk containing 2.5 ppm fluoride daily (T1), or every other day (T2), 5.0 ppm F daily (T3), or every other day (T4) or no treatment (T5). Results Enamel alterations were quantified by surface hardness recovery (%SHR) and transversal microradiography (TMR), and in dentine by TMR only. Data were analysed by ANOVA and Tukey's test (p < 0.05). For enamel, the highest %SHR was found for T1 and T3 compared to control, without significant differences between them. All groups showed positive values of ΔΔZ − T1 (247.3 ± 198.5); T2 (110.9 ± 303.2); T3 (226.0 ± 299.2); T5 (5.0 ± 288.0), except T4 (−274.5 ± 407.3). For dentine, the only group that presented remineralisation was T2 (350.0 ± 657.5). Conclusions Fluoridated milk daily seems to have higher remineralising effect on enamel than its use every other day. Dentine, does not seem to benefit from daily use of fluoridated milk.
Keywords: Caries; Dentine; Enamel; Fluoride; Milk; Remineralisation